2006
DOI: 10.1136/sti.2006.021196
|View full text |Cite
|
Sign up to set email alerts
|

Clients of sex workers in different regions of the world: hard to count

Abstract: Although errors of measurement and critical issues of definitions and interpretation exist, this compilation represents a first attempt to obtain reasonably coherent estimates of the proportion of men who were clients of sex workers at regional level. Large discrepancies between regions were found. Further improvements in national estimates will be critical to monitor coverage of HIV prevention programmes for sex workers and clients, and to improve estimates of national HIV infection prevalence levels in low a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 29 publications
(16 reference statements)
3
86
1
Order By: Relevance
“…This behaviour was more prevalent in older men, those who had not been married or were not living with a partner, had low levels of education, were not born in Spain, were members of a religious group, had started their economic https://doi.org/10.3989/ris.2018.76.2.17.47 activity at a very early age and those who had been drunk in the previous 30 days (Belza et al 2008). Other studies have shown different figures in Spain for the previous year: 9.9% (Hubert et al 1998) and 11% of men (Carael et al 2006), with Spain being in both cases one of the countries with the highest rates of men paying for sexual services. However, the diverse methodologies used to gather the data and the length of time taken to collect it makes it difficult to compare and make accurate estimations about this behaviour.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This behaviour was more prevalent in older men, those who had not been married or were not living with a partner, had low levels of education, were not born in Spain, were members of a religious group, had started their economic https://doi.org/10.3989/ris.2018.76.2.17.47 activity at a very early age and those who had been drunk in the previous 30 days (Belza et al 2008). Other studies have shown different figures in Spain for the previous year: 9.9% (Hubert et al 1998) and 11% of men (Carael et al 2006), with Spain being in both cases one of the countries with the highest rates of men paying for sexual services. However, the diverse methodologies used to gather the data and the length of time taken to collect it makes it difficult to compare and make accurate estimations about this behaviour.…”
Section: Introductionmentioning
confidence: 83%
“…From studies carried out in Europe (Hubert et al 1998;Carael et al 2006;Schei and Stigum 2010;Buttmann et al 2011;Jones et al 2015) which researched the behaviour of paying for sexual services, Spain shows the largest percentage obtained, and the data collected in this study continues to confirm this tendency; b) there are also few studies that focus on the men who pay for sexual services, given that in general academics and social researchers usually focus on the women who offer these sexual services -in this sense this study contributes by offering a typology of Spanish buyers which might be similar in other social contexts and which shows that there is no homogeneity in this masculine behaviour; and lastly, c) an attempt has been made to understand the opinions of Spanish men, particularly those who pay for sexual services, towards prostitution and trafficking for sexual exploitation. This subgroup of men could be an ally in the battle against human trafficking for sexual exploitation and we need to continue our research to be able to improve the sensitivity and awareness of this collective against this international crime which attacks the human rights of individuals, and especially of women and girls.…”
Section: Discussionmentioning
confidence: 99%
“…No national South African survey has measured the proportion of the male population engaging in commercial sex, but the average proportion of men reporting sex with sex workers in the last 12 months has been estimated at 6.3% in other Southern African countries (Caraël et al 2006). This is probably an underestimate of the true proportion of men having sex with sex workers, as men appear to underreport such sexual contacts in FTFIs (Des Jarlais et al 1999;Lau, Tsui, and Wang 2003;Morison et al 2001).…”
Section: Commercial Sexmentioning
confidence: 91%
“…However, if self-reported sexual behaviour data are heavily distorted by social desirability bias, as this analysis suggests, differences between two surveys -in the recruitment and training of interviewers, the precise wording of the questions, the positioning of the questions within the questionnaire, and the overall length of the questionnaire -can cause substantial differences in the reporting of certain behaviours (Curtis and Sutherland 2004). HIV/AIDS education programmes, by actively promoting reductions in particular risk behaviours, may also influence the extent of social desirability bias (Caraël et al 2006;Gregson et al 2002). In addition, our analysis shows that significant reductions in proportions of individuals reporting multiple partners, and significant increases in proportions reporting sexual abstinence, can be expected to occur as a result of HIV/AIDS morbidity and mortality, in the absence of any deliberate change in sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This causes a larger sexual network with increasing vulnerability of HIV/STD (12). Low level of knowledge regarding safe sex, educational level, sex with more than one partner are still dominant factors linked to spreading the disease in India (14,15,16).…”
Section: Introductionmentioning
confidence: 99%